PREVALENCE OF MICROALBUMINURIA IN TYPE - 2 DIABETES MELLITUS: A HOSPITAL BASED STUDY - Yadav, Dharamveer; Kochar, Bhawani; Mathur, Ankur; Chougle, Arun (International Journal of Research -GRANTHAALAYAH, 2017)
Aim: Microalbuminuria (MAU) has been shown to be a risk factor for nephropathy in patients with type 2 diabetes. In this study, we aimed to explore the association between MAU and other risk factors in the development of diabetic nephropathy with type 2 diabetes. Methods: Five twenty one patients with type 2 diabetes were recruited in this study. Medical records were used to collect data of age, duration of diabetes, Body Mass Index (BMI) and history of hypertension. Blood samples were collected after 12 hours overnight fasting to estimate fasting blood glucose (FBG), Glycosylated haemoglobin (HbA1C), serum creatinine, and serum uric acid. MAU was quantified using the dipstick method in early morning urine samples. Results: Out of 521 subjects 37.5% (186 subjects) were found to be suffering from MAU. Systolic and diastolic blood pressure (p<0.001), HbA1C (p<0.001) and fasting blood glucose (p<0.001) were significantly higher in subjects with MAU as compared to normoalbuminuria subjects. Further, on multiple logistic regression analysis it was observed that duration of diabetes, systolic and diastolic blood pressure, serum creatinine and FBG are associated with MAU. Conclusion: The overall prevalence of the MAU was high in the present study, which necessitates for early detection of nephropathy to reduce the burden of diabetes induced kidney disease in the future.